The 'Blackwood' Group - Douglas, George, 1856-1935 (Salt Lake City, UT : Project Gutenberg, 2011)
"The 'Blackwood' Group" by Sir George Douglas is a historical account written in the late 19th century. The work explores the lives and contributions of notable Scottish authors connected to the Blackwood publishing house, particularly focusing on John Wilson, known as "Christopher North." The book delves into the dynamic literary scene of the era, celebrating the influence and legacy of these figures in Scottish literature. The opening of the narrative introduces John Wilson, detailing his early life, education, and the formative experiences that shaped his personality and aspirations as a writer. It highlights his robust childhood, keen intellect, and love for nature and sports, alongside his struggles with unrequited love and his eventual rise to prominence in Edinburgh's literary circles. Douglas sets a foundation by outlining Wilson's pivotal connection to Blackwood's Magazine and hints at the vibrant interplay of literary personalities during a time of great cultural significance in Scotland. (This is an automatically generated summary.)
Release date is 2011-01-07
E-text prepared by Susan Skinner and the Online Distributed Proofreading Team
Keywords: Wilson, John, 1785-1854; Galt, John, 1779-1839; Moir, D. M. (David Macbeth), 1798-1851; Ferrier, Susan, 1782-1854; Scott, Michael, 1789-1835; Hamilton, Thomas, 1789-1842